2008
DOI: 10.1086/526792
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Human Papillomavirus and HIV among Young Women in Kampala, Uganda

Abstract: The prevalence of HPV infection is high among young women in Kampala, Uganda. Clinics for teenagers provide an opportunity to monitor the impact of HPV vaccines and, possibly, to catch up unvaccinated young women who have recently become sexually active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
3
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 31 publications
6
53
3
7
Order By: Relevance
“…High prevalence of HPV in women with a low SES has been shown in a few studies (Hildesheim et al, 1993;LazcanoPonce et al, 2001), but has not been confirmed in others (Deacon et al, 2000;Shapiro et al, 2003;Khan et al, 2005;Banura et al, 2008;Hibbitts et al, 2008).…”
mentioning
confidence: 95%
“…High prevalence of HPV in women with a low SES has been shown in a few studies (Hildesheim et al, 1993;LazcanoPonce et al, 2001), but has not been confirmed in others (Deacon et al, 2000;Shapiro et al, 2003;Khan et al, 2005;Banura et al, 2008;Hibbitts et al, 2008).…”
mentioning
confidence: 95%
“…[2][3][4][5] In many parts of Africa, ICC is a leading cause of cancer death in women. [2][3][4][5][6][7] Though rates of ICC vary considerably in different sub-regions, cervical cancer ranks first or second (after breast cancer) in all individual sub-Saharan African countries. 8 In subSaharan Africa, over 70,000 new cases occur annually with an age standardized incidence rate of 31.0 per 100,000 women.…”
mentioning
confidence: 99%
“…The overall HPV prevalence was 64% in post-partum women Previous HPV prevalence studies were conducted in women from the sexually transmitted disease clinic at the main hospitals in Kampala, Uganda, as well as at an adolescent clinic in the suburbs. The reported incidence of HPV infection in these studies ranged from 75% in women aged 12-25 years seen at an adolescent clinic 40 to 46% in women 18-55 years of age presenting in the STD clinic, 41 suggesting clearance of most HPV infections with age. The overall HPV prevalence detected in our study of women aged 18-30 years old is intermediate between these two groups, supporting this concept.…”
Section: Discussionmentioning
confidence: 91%